Psychological Safety as a Driver of Employee Voice: A Systematic Literature Review - Muhammad Irfan Akbar; Fiona Niska Dinda Nadia (Jurnal Ragam Pengabdian, 2026)
This study aims to regularly examine the relationship between psychological safety and employee voice in an organizational context. This study employed a Systematic Literature Review (SLR) following PRISMA guidelines. Literature was retrieved from the Scopus database using keywords related to psychological safety and employee voice. Based on predetermined inclusion and exclusion criteria, 13 peer-reviewed quantitative empirical articles published between 2019 and 2025 were selected. The selected studies were analyzed using narrative and thematic synthesis to identify patterns, roles, and relationships between variables. The findings indicate that psychological safety consistently has a positive influence on employee voice across various organizational environments and cultures. Psychological safety primarily serves as a mediator linking leadership style, organizational systems, and social relationships with employee voice. Several studies also identified psychological safety as a moderator that strengthens or weakens the effectiveness of organizational practices in encouraging employee voice. Employees are more likely to voice ideas, suggestions, and concerns when they perceive a psychologically safe work environment. This study is limited to a single database (Scopus) and focuses only on quantitative empirical studies, which may limit the generalizability of the findings. This study contributes to the literature on organizational behavior and human resource management by synthesizing empirical evidence on the role of psychological safety in promoting employee voice and offering practical implications for organizational leadership. Its novelty lies in regularly mapping psychological safety as a mediator and moderator in the employee voice literature.